Cultivating a Dialogue: Rewilding, Heritage Landscapes, and Belonging - Tokarski, Mateusz; Gammon, Andrea R. (The Trumpeter, 2016)
Rewilding in Europe currently presents a threat to long established forms of agriculture like upland sheep farming. Some rewilders, recognizing the heritage value of these farming practices, have proposed policy solutions to satisfy both the needs of farmers and the plans of rewilders. Such approaches, though striving for peaceful resolution of landscape conflicts, nevertheless overlook one crucial possibility: that both farmers and rewilders have something to learn from each other. By exploring philosophical ideas on dialogue, we propose that by engaging in real dialogue with traditional farming practices, conservation approaches like rewilding can learn a lot about some of the most fundamental concerns motivating conservation. This however demands laying oneself open to possible criticism and being open to the possibility of transformation.